A comprehensive review on anaerobic digestion of organic fraction of municipal solid waste. (March 2021) - Zamri, M.F.M.A.; Hasmady, Saiful; Akhiar, Afifi; Ideris, Fazril; Shamsuddin, A.H.; Mofijur, M.; Fattah, I. M. Rizwanul; Mahlia, T.M.I.
Abstract: This article aims to comprehensively review the anaerobic digestion (AD) process utilising the organic fraction of municipal solid waste (OFMSW) substrate. The AD of OFMSW has received considerable attention due to its significant energy and nutrient recovery as well as its greenhouse gas (GHG) mitigation potential. AD is a biological process involving treating and stabilising organic matter in the absence of oxygen accomplished by a consortium of microorganisms and occurs under hydrolysis, acidogenesis, acetogenesis, and methanogenesis phases. The hydrolysis phase is recognised as the primary rate-limiting step. Thus, exploring the ways to speed up the hydrolysis process will maximise biogas production. The key factors affecting the digestion efficiency include feedstock quality, pre-treatment process, design and selection of digestion process and process conditions including pH, temperature, carbon to nitrogen (C: N) ratio, organic loading rate and hydraulic retention time. The review reveals that solid-state anaerobic digestion (SSAD) is best suited for OFMSW due to its high solid concentration (>15%) and better process performance. The continuous digestion with thermophilic temperatures was found to be the best condition for high solid AD process. The plug flow and continuous stir tank reactors were the best performing options to control the biological conditions for the digestate post-treatment. Proper selection of the parameters for the whole process is crucial in ensuring process feasibility and economic sustainability of AD of OFMSW. The study revealed that the AD of OFMSW could play a significant role to mitigate waste and waste-related problems. Highlights: Studies on organic fraction of municipality solid waste are reviewed. Pretreatment is required to achieve optimum results in anaerobic digestion. The digestion operating conditions significantly controls the biogas output. The products of digestate require post-treatment for maximised output.